Odpowiedzi

2010-03-23T11:05:22+01:00
4
a)
6(x+y)=10y
y-x=0,5

6x+6y=10y
y=0,5+x

6x+6(0,5+x)=10(0,5+x)
y=0,5+x

6x+3+6x=5+10x
y=0,5+x

12x-10x=5-3
y=0,5+x

2x=2/:2
y=0,5+x

x=1
y=1,5

c)
2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

7x+7y=42
-11x+23y=-32

7x=42-7y /:7
-11x+23y=-32

x=6-y
-11(6-y)+23y=-32

x=6-y
-66+11y+23y=-32

x=6-y
34y=-32+66

x=6-y
34y=34 /:34

x=6-y
y=1

x=5
y=1

d)
y/2+x/4-1/5(x+2)=1,1
x-2y+4=x/2+3/4(y-0,5)

0,5y+0,25x-0,2(x+2)=1,1
x-2y+4=0,5x+0,75(y-0,5)

0,5y+0,25x-0,2x-0,4=1,1 /*100
x-2y+4=0,5x+0,75y-0,375/*1000

50y+25x-20x-40=110
1000x-2000y+4000=500x+750y-375

5x+50y=150 /5
500x-2750y=--4375

x=30-10y
500(30-10y)-2750y=-4375

x=30-10y
15000-5000y-2750y=-4375

x=30-10y
-7750y=-19375 /:(-7750)

x=30-10y
y=2,5

x=30-10*2,5
y=2,5

x=5
y=2,5